DAYA HAMBAT INFUSA BIJI PINANG (Areca catechu L.) TERHADAP BAKTERI Staphylococcus aureus - Maryam Ulfah Wael; Sri Sinto Dewi; Endang Tri Wahyuni Maharani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The objective of this research is to measure and analyze the difference of inhibition concentration of areca nuts concentration 2%b/v, 3%b/v, 4%b/v, 5%b/v and 6%b/v on the growth of S.aureus. The sample used in this research is areca nuts (Areca catechu L.) with the object of research S.aureus that has equalized turbidity with Mc Farland standard 0.5. Antibacterial testing is done by diffusion method (wells). The results showed that areca nuts can inhibit S.aureus bacteria with area of inhibit zone for concentration 2% b/v, 3% b/v, 4% b/v, 5% b/v and 6% b/v is 14,5 mm, 14,6 mm, 16 mm, 18 mm and 18 mm. Result of normality test Kolmogorov-Smirnov S.aureus (p=0,691) the values obtained are normally distributed. The homogenity test of S.aureus is not homogeneous, Then proceed with non parametric test that is Kruskal Wallis (p=1,000) the values obtained showed no significant difference to mean inhibition zone diameter between concentrations 2%b/v, 3%b/v, 4%b/v, 5%b/v and 6%b/v areca nuts infusion against S. aureus bacteria. Keywords: Areca nuts infusion, Staphylococcus aureus, Inhibition